2020
DOI: 10.1109/tcomm.2019.2945781
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Successive Interference Cancellation Strategies in NOMA for Enhancing the Spectral Efficiency of CoMP Systems

Abstract: The densification of mobile networks should enable the fifth generation (5G) mobile networks to cope with the ever increasing demand for higher rate traffic, reduced latency, and improved reliability. The large scale deployment of small cells and distributed antenna systems in heterogeneous environments will require more elaborate interference mitigating techniques to increase spectral efficiency and to help unlock the expected performance leaps from the new network topologies. Coordinated multi-point (CoMP) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Moreover, to take advantage of the cooperation between the cells and to properly manage inter-cell interference, cell-center users from cell 1 and 2 should be considered as well. The interference management can be done through NOMA pairing of users from both cells, as was done in [22]. For this purpose, we focus our study on a three-user NOMA cluster formed by a triplet of users selected from regions 1, 2 and 3 of the two cells, as shown in Fig.…”
Section: System Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, to take advantage of the cooperation between the cells and to properly manage inter-cell interference, cell-center users from cell 1 and 2 should be considered as well. The interference management can be done through NOMA pairing of users from both cells, as was done in [22]. For this purpose, we focus our study on a three-user NOMA cluster formed by a triplet of users selected from regions 1, 2 and 3 of the two cells, as shown in Fig.…”
Section: System Modelmentioning
confidence: 99%
“…It is assumed that the information to be transmitted for each user is made available at the level of the BS and MBS through the backhaul link, enabling DPS and JT serving in the system. JTmode is used in the remainder of the study, given its superior performance to DPS, as shown in [22]. FIGURE 1: Illustration of the two-cell JT system with the functional base station a 1 , the saturated BS in cell 2, the UAV working as MBS a 2 , and the three colored user regions.…”
Section: System Modelmentioning
confidence: 99%
See 3 more Smart Citations